1987
DOI: 10.5860/crl_48_04_339
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Online Systems in U.S. Academic Libraries

Abstract: A survey of online systems in U.S. academic libraries was conducted to gather information on acquisitions, serials, circulation, cataloging, interlibrary loan, and integrated systems. Libraries reported on present systems and future plans, methods of financing, and use of systems personnel, as well as backup systems, type of computer, source for system, and functions within systems. Survey results indicate that 15% of libraries have no online systems and that 16.2% plan no additional ones. Cataloging and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It would appear that, because each OPAC is following different normalization rules for searching and indexing, and different filing rules for arranging retrieved headings or records, the cross-reference rules cannot yet be optimally standardized. The situation is further complicated by the fact that the majority of libraries do not yet have online public access catalogs, and perhaps many of them will never be able to afford them (Sitts, 1985;Camp et al, 1987). Card and COM catalogs still need cross references designed for linear alphabetical sequences of headings.…”
Section: Findings Of Previous User Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It would appear that, because each OPAC is following different normalization rules for searching and indexing, and different filing rules for arranging retrieved headings or records, the cross-reference rules cannot yet be optimally standardized. The situation is further complicated by the fact that the majority of libraries do not yet have online public access catalogs, and perhaps many of them will never be able to afford them (Sitts, 1985;Camp et al, 1987). Card and COM catalogs still need cross references designed for linear alphabetical sequences of headings.…”
Section: Findings Of Previous User Studiesmentioning
confidence: 99%
“…For this reason, this review will concentrate on OPAC user interface features that are influenced by record design. Camp et al have found that only slightly over 12% of academic libraries have online public access catalogs, but 65% currently without an OPAC plan to implement one (Camp et al, 1987). The improvement of user interfaces could benefit the users of all these future systems.…”
Section: Introductionmentioning
confidence: 99%